2018
DOI: 10.14710/jitaa.43.2.184-192
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Lactobacillus plantarumU40 on the in vitro rumen fermentation quantified with real-time PCR

Abstract: ABSTRAKTujuan dari penelitian ini adalah untuk menganalisa daya tahan L. plantarumU40 menggunakan real-time PCR dalam fermentasi rumen in vitro. Desain penelitian yang digunakan adalah Rancangan Acak Kelompok dengan 3 perlakuan dan 4 ulangan. Perlakuan yang diberikan adalah kontrol, inokulasi dengan L. plantarumU40 danL. plantarumU40 + glukosa. Perlakuan dengan inokulasi menghasilkan populasi L. plantarumU40 yang lebih tinggi. Setelah 8 jam inkubasi, pemberian glukosa cenderung menurunkan populasi L. plantarum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This bacterium is native to rumen ecology and binds to the rumen epithelium as well (Stewart, 1992). The research conducted by Astuti et al (2018b) using in vitro gas production technique and real-time PCR concluded that L. plantarum can survive in the rumen. Using 1.5×10 8 CFU/mL commercial strain of L. plantarum in the rumen for in vitro fermentation enhances OMD and total VFA (Direkvandi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium is native to rumen ecology and binds to the rumen epithelium as well (Stewart, 1992). The research conducted by Astuti et al (2018b) using in vitro gas production technique and real-time PCR concluded that L. plantarum can survive in the rumen. Using 1.5×10 8 CFU/mL commercial strain of L. plantarum in the rumen for in vitro fermentation enhances OMD and total VFA (Direkvandi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%